2011
DOI: 10.4269/ajtmh.2011.10-0429
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic Cerebrovascular Events and Neurocysticercosis: A Case Report and Review of the Literature

Abstract: Abstract. Cerebrovascular complications have been reported to occur in patients with neurocysticercosis (NCC). We report a patient who presented with relapsed subarachnoid hemorrhage possibly linked to NCC. In addition, we performed a literature review of all of the reported cases of aneurysmal and non-aneurysmal hemorrhagic cerebrovascular events associated with NCC. We identified 11 such cases. The majority of the individuals were young males (mean: 38 years; 70% males). Four cases (36%) had aneurysms. Four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…Seizures can arise, but less frequently. Subarachnoid cysts can generate an inflammatory response that can then lead to chronic arachnoiditis, which then may become complicated by hydrocephalus, meningitis, stroke and vasculitis …”
Section: Discussionmentioning
confidence: 99%
“…Seizures can arise, but less frequently. Subarachnoid cysts can generate an inflammatory response that can then lead to chronic arachnoiditis, which then may become complicated by hydrocephalus, meningitis, stroke and vasculitis …”
Section: Discussionmentioning
confidence: 99%
“…Almost all clinical presentations of stroke can be seen in epileptic patients having SNCC [27,41,[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65]. Despite the increasing number of reports on haemorrhagic stroke to the medical literature [19, 20, 23, 24, 26, 27, 29-31, 37-41, 47-62], the prevalence of stroke secondary to NCC remains higher in IS secondary to infectious vasculitis.…”
Section: Strokementioning
confidence: 99%
“…However, large infarcts related to the occlusion of the middle cerebral artery or even the internal carotid artery have also been reported [50]. Viola et al [57] reported a patient who presented with relapsed subarachnoid haemorrhage possibly linked to NCC. In addition, they performed a literature review of all of the reported cases of aneurysmal and non-aneurysmal haemorrhagic cerebrovascular events associated with NCC until year 2011 and identified 11 such cases.…”
Section: Strokementioning
confidence: 99%
See 1 more Smart Citation
“…Hemorrhagic stroke can also occur in NCC . The above‐described inflammatory damage to the endothelium leads to oedema, thrombosis, weakening of the arterial wall and subsequent formation of fusiform pseudoaneurysms that may eventually break .…”
Section: Clinical Manifestations Of Nccmentioning
confidence: 99%